Meningeal Carcinomatosis in Bladder Transitional Cell Carcinoma - Akhavan, Ali; Binesh, Fariba; Ghannadi, Fazlollah (Reports of Radiotherapy and Oncology, 2025)
Meningeal carcinomatosis is a rare event in bladder transitional cell carcinoma. In this report, we present a man with transitional cell carcinoma who developed brain metastasis followed by spinal and leptomeningeal involvement.